Le contrôle du corps des femmes à travers l’histoire. Essai de mise en perspective de la question de la santé sexuelle et reproductive des femmes dans le monde arabe - Sophie Bessis (L’Année du Maghreb)
The control of women's bodies is as old as the male domination itself, all turned towards a central goal, the control of motherhood. This control is exercised according to particular modalities in different civilizations but always aims to control female sexuality so as to ensure the reproductive function for the benefit of the group of males. The customary practices of the most diverse societies have focused on codifying the terms of control. As for religions, especially the three monotheistic religions, but not only, they served to sanctify the processes of domination through which patriarchal control is exercised. Religions and customs intertwined, one reinforcing the others, thus constructed normative devices of domination. Thus they legislate all on the bodies of women, enclosing the latter in a corset of obligations and prohibitions. The symbolic valorization of maternal function and the demonization of femininity are part of this apparatus of constraint. This corset was forced to yield (more or less) to secularized and secularized societies where religious prohibitions were gradually disconnected from the positive law. While in Europe, advances have been proportional to secularization processes, the prohibitions resist in the Arab world given the slowness of these processes and the regressions that may have affected them. We will review the multiplicity of religious injunctions to procreation and prohibitions on the reproductive and sexual autonomy of women. We will focus more on their permanence in the Arab-Muslim context, to show that the secularization of laws and social practices is a necessary condition for the full exercise of women's sexual rights, even if it is not enough to ensure this liberation alone.